Investing Strategically in Higher Education : Aligning Public Funding with Policy Objectives - World Bank Group (World Bank, Washington, DC, 2017)
Linking higher education finance and policy, referred to as strategic financing, is increasing in popularity throughout Central Europe and the Baltic Countries. Strategic financing essentially implies that public funding mechanisms are informed by and aligned with specific higher education policy objectives. Governments are asking how the funding strategy can be more supportive of policy objectives. Can funding formulae, for instance, be modified strategically to help realize certain policy objectives? If a government is seeking to enroll more science, technology, engineering and math (STEM) students, for example, could allocating a premium to higher education institutions (HEIs) per STEM student help achieve the policy objective? Like many countries around the work, Central European and Baltic countries are exploring how different financing modalities can provide additional leverage in steering their higher education sector towards specific policy objectives. In recent years, many Central European and Baltic countries are facing common economic, socio-political, and demographic factors. These common challenges can broadly be categorized into three main themes: challenging economic environment; increasing European integration; and declining demographic trends. First, the region still faces fiscal constraints as it emerges from the global economic slowdown. Such economic trends have placed downward pressure on public higher education budgets and increased the call for collaboration between higher education and the labor market. Second, national higher education policies across Central Europe and the Baltic countries are impacted by a broader European policy environment, including the European Higher Education Area. Supranational initiatives, such as the EU’s Education and Training 2020 Strategy, Horizon 2020, and its Modernization Agenda for Higher Education, as well as the intergovernmental Bologna Process strongly influence national higher education policies. Third, a declining population in Europe is shrinking the number of working- and student-age people. After decades of growth in the higher education sector, the number of new students participating in higher education is slowly declining.